Association of caries experience in 12-year-old children in Heidelberg, Germany, and Montpellier, France, with different caries preventive measures - Schulte A, Rossbach R, Tramini P. (Blackwell Synergy, 2001)
In Germany and France, different approaches to oral health promotion have been chosen. Objectives: It was the aim of the present study to assess whether different preventive measures were positively or negatively associated with caries experience in 12-year-old children in Heidelberg, Germany, and in Montpellier, France.